2011
DOI: 10.2478/v10078-011-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of Platelet Rich Plasma in Sports Medicine

Abstract: Any new method of treatment is associated with high expectations for its success, particularly if the therapy is based not only on the premise of achieving a symptomatic effect, but also improving functional quality and repairing structurally damaged tissues. Platelet Rich Plasma (PRP) application was shown to be a successful catalyst in the healing process for a wide variety of conditions in animal and human models. However, its use has been controversial due to many types of the PRP definition, optimal conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The growth factors released by PRP have been discussed in great detail within the literature (Lubkowska et al 2012;Pavlovic et al 2016;Fernandes and Yang 2016;Parrish and Roides 2018) and have been shown to promote cell recruitment, proliferation and angiogenesis resulting in a reduction in the critical regulators of the inflammatory process and a decrease in the expression of inflammatory enzymes (Table 2) (van Buul et al 2011). PRP may induce a regenerative response by improving the metabolic functions of damaged structures (Ficek et al 2011;Chen et al 2018) and has been shown to have a positive effect on chondrogenesis and mesenchymal stem cell proliferation (Kabiri et al 2014).…”
Section: Current Knee Osteoarthritis Incidence and Management Strategiesmentioning
confidence: 99%
“…The growth factors released by PRP have been discussed in great detail within the literature (Lubkowska et al 2012;Pavlovic et al 2016;Fernandes and Yang 2016;Parrish and Roides 2018) and have been shown to promote cell recruitment, proliferation and angiogenesis resulting in a reduction in the critical regulators of the inflammatory process and a decrease in the expression of inflammatory enzymes (Table 2) (van Buul et al 2011). PRP may induce a regenerative response by improving the metabolic functions of damaged structures (Ficek et al 2011;Chen et al 2018) and has been shown to have a positive effect on chondrogenesis and mesenchymal stem cell proliferation (Kabiri et al 2014).…”
Section: Current Knee Osteoarthritis Incidence and Management Strategiesmentioning
confidence: 99%
“…Platelet‐rich plasma contains a high concentration of growth factors that promote proliferation, migration, cell differentiation, and angiogenesis 31 . Platelet‐rich plasma has been used widely in sports medicine, dental medicine, wound repair, and alopecia with growing evidence of its efficacy in recent 30 years 31,32 . Because plantar fasciitis represents a chronic, degenerative process, theoretically platelet‐rich plasma could be beneficial for tissue repair and regeneration in the plantar fascia.…”
Section: Discussionmentioning
confidence: 99%
“…31 Platelet-rich plasma has been used widely in sports medicine, dental medicine, wound repair, and alopecia with growing evidence of its efficacy in recent 30 years. 31,32 Because plantar fasciitis represents a chronic, degenerative process, theoretically platelet-rich plasma could be beneficial for tissue repair and regeneration in the plantar fascia. However, there was no standardized method in preparing platelet-rich plasma across these studies, and there is no consensus regarding the best concentration or volume for injection in plantar fasciitis or other musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PRP/PRF used along with collagen membranes was extensively applied for regeneration of periodontal ligament and alveolar bone as a part of guided tissue regeneration procedures in periodontics and oral surgery. PRP therapy was shown to be a successful promoter in the healing process (Ficek, Kaminski, Wach, Cholewinski, & Cieszczyk, 2011; Khodakaram-Tafti, Mehrabani, & Shaterzadeh-Yazdi, 2017). PRP and its associated formulations have yet to show promise in dental pulp regeneration, though.…”
Section: Biomaterials-based Scaffolds For Regenerating the Dentin-pulmentioning
confidence: 99%